Eine siedlungsstrukturelle Wohnumfeldtypologie für Nordrhein-Westfalen. Methodik, Charakterisierung und Anwendung - Hölzel, David J. (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
Typologies of urban form facilitate the understanding of and communication on complex spatial issues in the context of spatial planning, research and policy. Currently, in Germany they are primarily available at federal and regional level, while small-scale typologies of urban form of comparable generalizability are scarce which complicates communication about spatial and space-related issues. Residential environments are an important context of everyday activity spaces and therefore, a typology of residential environments helps improve the understanding of the nexus between space and society. This paper aims to derive a typology of residential environments based on a high number of randomly generated locations in North Rhine-Westphalia and open access data on urban form. By linking the typology to the BBSR-“Stadt- und Gemeindetypen” and the RegioStaR typologies, this paper shows how the typology of residential environments may be linked to large-scale typologies. The paper further demonstrates its applicability in two very different subject areas by performing exemplary comparisons of the contextual factors of children’s mobility in Dortmund and political voting behaviour in Aachen, Germany. The typology is made freely available for further use in other studies.
Keywords: Settlement structure; Residential Environments; Indicators; Monitoring; Spatial Typology; Elections; Children